HIRARKI SYARI'AT DAN HAKIKAT DALAM KAJIAN TASAWUF - Muhammad Liwa’ uddin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2015)
Sharia, congregations, and nature is the station-maqam in Sufism. About maqam is often a debate among Muslims, especially the laity. They thought that a person who has reached the rank of nature, it is no longer necessary to run the teachings of the Shari'ah. They are also confused by the claims of people who feel they have reached the station of nature that feels no need to run the Shari'a. Such understanding is of course to be straightened using explanations that are scientifically and rationally. This study tried to review the understanding of three-maqam above and the relationship between these three work together and complement each other.